A longitudinal comparison of retention in buprenorphine and methadone treatment for opioid dependence in New South Wales, Australia. (April 2015) - Burns, Lucy; Gisev, Natasa; Larney, Sarah; Dobbins, Timothy; Gibson, Amy; Kimber, Jo; Larance, Briony; Mattick, Richard P.; Butler, Tony; Degenhardt, Louisa
Abstract: Background and Aims: To examine characteristics of first‐time methadone and buprenorphine clients and factors associated with risk of leaving first treatment in New South Wales (NSW), Australia. Design: Retrospective linkage study of opioid substitution therapy (OST) treatment, court, custody and mortality data. Setting: NSW, Australia. Participants: First‐time OST entrants (August 2001–December 2010). Measurements: Characteristics of clients were examined. Time‐dependent Cox models examined factors associated with the risk of leaving first treatment, with demographic, criminographic and treatment variables jointly considered. Interactions between medication and other variables upon risk of leaving treatment were examined. Findings: There were 15 600 treatment entrants: 7183 (46%) commenced buprenorphine, 8417 (54%) commenced methadone; the proportion entering buprenorphine increased over time. Those starting buprenorphine switched medications more frequently and had more subsequent treatment episodes. Buprenorphine retention was also poorer. On average, 44% spent 3+ months in treatment compared with 70% of those commencing methadone; however, buprenorphine retention for first‐time entrants improved over time, whereas methadone retention did not. Multivariable Cox models indicated that in addition to sex, age, treatment setting and criminographic variables, the risk of leaving a first treatment episode was greater on any given day for those receiving buprenorphine, and was dependent on the year treatment was initiated. There was no interaction between any demographic variables and medication received, suggesting no clear evidence of any particular groups for whom each medication might be better suited in terms of improving retention. Conclusions: Although retention rates for buprenorphine treatment have improved in New South Wales, Australia, individuals starting methadone treatment still show higher retention rates.